STUDI PREFORMULASI: VALIDASI METODE SPEKTROFOTOMETRI OFLOKSASIN DALAM LARUTAN DAPAR FOSFAT - Budipratiwi Wisudyaningsih (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2012)
A simple, accurate, precise, and economic UV-spectrophotometric method was developed for the estimation of ofloxacin in phosphate buffer at pH 3,0; 7,4; and 12,0. Ofloxacin solubility is dependent on pH of the solvent due to its amphoteric properties. Ofloxacin has absorbance maxima at 295 nm in pH 3,0; 288 nm in pH 7,4; and 290 nm in pH 12,0. Linearity was obtained in the concentration range of 4-10 g/mL for each pH. Ofloxacin detection limit at pH 3,0 was 150 g/L, at pH 7,4 and pH 12,0 were 10 g/L, respectively. Recovery values at three pH conditions were in the range 89,93-104,25%. The results of analysis have been validated statistically and by recovery studies.